Navigating the uncertainty of health advocacy teaching and evaluation from the trainee's perspective. (2nd January 2022) - Endres, Kaitlin; Burm, Sarah; Weiman, Daniel; Karol, Dalia; Dudek, Nancy; Cowley, Lindsay; LaDonna, Kori
Abstract: Background: There may be no competency more shrouded in uncertainty than health advocacy (HA), raising questions about the robustness of advocacy training in postgraduate medical education. By understanding how programs currently train HA, we can identify whether trainees' learning needs are being met. Methods: From 2017 to 2019, we reviewed curricular documents across nine direct-entry specialties at all Ontario medical schools, comparing content for the HA and communicator roles to delineate role-specific challenges. We then conducted semi-structured interviews with trainees ( n  = 9) and faculty ( n  = 6) to review findings and discuss their impact. Data were analyzed using thematic content analysis. Results: Curricular documents revealed vague objectives and ill-defined modes of assessment for both intrinsic roles. This uncertainty was perceived as more problematic for HA, in part because HA seemed both undervalued in, and disconnected from, clinical learning. Trainees felt that the onus was on them to figure out how to develop and demonstrate HA competence, causing many to turn their learning attention elsewhere. Discussion: Lack of curricular focus seems to create the perception that advocacy isn't valuable, deterring trainees—even those keen to become competent advocates—from developing HA skills. Such ambivalence may have troubling downstream effects for both patient care and trainees' professional development.